Estrategias financieras y su efecto en la rentabilidad a corto plazo de la empresa internegocios de hierro S.A., cantón Quevedo, Año 2015 - Ruiz Ambrosi, Joselyn Verónica (2016)
The present research was conducted in the Canton Quevedo in Internegocios Company Iron SA, Addressed to demonstrate the need for financial strategies, areas Promoting operational, administrative, Marketing subparagraph which comply Agreement at: regulations Such established enterprises para fin to determine S. Improve profitability and propose viable way, and improve processes and increase the productivity of the company ,: The research will also provide a clear view on the financial strategies that should be implemented para to increase profitability m. For registration of the Information UN survey questionnaire EMPLOYMENT Customers of Internegocios Iron Company S.A., and determine criteria S. Do About Quality, Price, and satisfaction for the given service. After the investigation it was determined S. currently 86% of customers Internegocios SA Iron Company, said they are satisfied with the service you have given them the company also established the 86% that if applied right Company financial strategies could increase profitability. : Besides financial strategies implemented in Internegocios Iron Company SA Were the creation of two savings funds, provided on the Internet, Consulting, Investment and establish a vision, plus the personalities responsible for performing financial strategies in the Company son counter and the administrator. Also the results of the indicators of profitability Were Applied to iron Internegocios S.A, the company noted that the comparison of the years 2013-2014 Business Revenue increased by 2.7%.